A Rapid Seedling Assay for Determining Sweetpotato Resistance to Fusarium Wilt. Issue 4 (3rd May 2018) - Yang, Zhijian; Lin, Yuli; Chen, Haizhou; Zou, Weikun; Wang, Songliang; Guo, Qimao; Chen, Xuanyang
Abstract : Fusarium wilt, caused by Fusarium oxysporum f. sp. batatas (Woolenw.) W. C. Snyder & H. N. Hansen (abbreviated as "Fob"), is a devastating disease that can cause sweetpotato [ Ipomoea batatas (L) Lam.] yield losses of up to 50%. A rapid and efficient assay can expedite the selection of Fusarium wilt‐resistant cultivars. A rapid seedling assay was developed to evaluate sweetpotato resistance to Fusarium wilt. Seedlings of three cultivars—JinShan 57 (highly resistant), JinShan 696 (moderately resistant), and XinZhongHua (highly susceptible)—were grown in suspensions containing different conidial concentrations of Fob. Inoculation with a Fob conidial suspension of 1 × 10 5 conidia mL −1, incubation of inoculated plants at 28°C, and assessment of disease development 12 d after inoculation provided optimal results. Resistance of 28 sweetpotato advanced breeding selections was evaluated in 2014 and 2015 using the rapid method and a conventional field test. These tests confirmed the reliability of the rapid method. This study demonstrates that the new assay is rapid, efficient, and can facilitate screening of large numbers of sweetpotato cultivars and selections for Fob resistance.